PERAN STRATEGIS PENGEMBANGAN MARKETING SKILL DALAM MEMBANGUN BRAND AWARENESS DAN DAYA SAING UMKM DI ERA PERSAINGAN DIGITAL YANG SEMAKIN KOMPETITIF - Cici El Dirrah Syafitri Simanungkalit; Zuhrinal M Nawawi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The digital era presents both challenges and opportunities for Micro, Small, and Medium Enterprises (MSMEs), particularly in marketing and business competitiveness. This study aims to analyze the strategic role of developing marketing skills in building brand awareness and enhancing MSME competitiveness amidst increasingly intense digital competition. The research uses a qualitative approach with literature review as the basis of analysis. The findings indicate that mastery of digital marketing skills such as the use of social media, content management, brand communication strategies, and consumer behavior analysis significantly contributes to increasing the visibility and competitiveness of MSMEs. Strong brand awareness enables MSMEs to gain consumer trust, expand their market reach, and sustain themselves in a highly dynamic digital ecosystem. Therefore, developing marketing skills is a strategic necessity for MSMEs not only to survive but also to grow sustainably.